Communication Strategies of Brand Management and Online Marketing of Digital Products - Fayvishenko, Diana; Mitchuk, Olha; Lorvi, Iryna; Konopliannykova, Marianna; Chernobrovkina, S. V.; Sytnyk, Oleksii (My University, 2023)
The peculiarities of the communication strategy of brand management and Internet marketing of digital products play a key role in the commercial activities of the enterprise and its positioning in the information environment. The modern practice of using digital technologies in marketing is key to improving the competitive activity of an enterprise, covering the market, and forming its customer base of consumers. The article aims to conduct a study on the implementation of communication strategies for brand management and Internet marketing of digital products in a dynamic market and rapid development of information technologies. The research is concerned with the qualitative allocation of financial resources and the search for optimal means of implementing digital tools for commercial activities. The article examines the peculiarities of the theoretical concept of the communication strategy of brand management and Internet marketing, dividing it into its key stages and stages of implementation. An important direction in the study is the analysis of theoretical provisions of brand management, control of brand development practice, its formation, and promotion of the perception of the enterprise’s image in the information environment. Due attention is paid to the issue of using appropriate means of modern marketing policy for enterprises and businesses engaged in the sale of digital products. The practice of using creative approaches in marketing activities and the use of non-standard means of organizing marketing activities is studied. The obtained results of the study can be used to improve the quality of implementation of the communication strategy of brand management and Internet marketing of digital products in the context of the rapid development of information technologies.
Keywords: brand management; information technologies; communication strategy; internet marketing; digital marketing; social media; search engine optimization; commercial activities